Keragaan Usahatani Kelapa dengan Tanaman Pisang dan Ubi Kayu di Minahasa Utara - DANIEL J. TORAR; A. LAY (Buletin Palma, 2010)
Performance of Coconut Farming with Banana Plant and Cassava in North MinahasaThe research was done from June to July 2010 in Maumbi village, Kalawat Sub District, North Minahasa District. The respondent were chosen by using Purposive Random sampling method. Data were collected as follow : plant cultivation and yield processing, and its price. The objectives of the research was to determine the productivity and farme’r income on multiply crops planting system consisting of coconut and banana, coconut and cassava. Research result showed that the higher the plant production the higher the farmer’s income. Farmers having coconut palm with production of 2 ton/ha, applying monoculture planting system and sold coconut products in forms of copra and charcoal had a net income Rp. 11,26 millon/ha/year, while those who sold coconut products in form of coconut without the husk had a net income to Rp 7,2 millon/ha/year. This income was categorized lower than minimum regional income. Intrercropping coconut with banana and cassava with production 2 ton copra/ha/year would raise farmer income up to Rp. 24 millon/ha/year, a better family income.